1998
DOI: 10.1002/j.1550-8528.1998.tb00317.x
|View full text |Cite
|
Sign up to set email alerts
|

Lactate Production from Glucose and Response to Insulin in Perifused Adipocytes from Mesenteric and Epididymal Regions of Lean and Obese Rats

Abstract: KING, JOYCE L, MARIO DIGIROLAMO. Lactate production from glucose and response to insulin in perifused adipocytes from mesenteric and epididymal regions of lean and obese rats. Obes Res. 1998;6:69-75. Lactate, an important metabolic substrate for peripheral tissues and the liver, is released in significant amounts from adipose tissue. Using a perifusion system, we measured lactate production from glucose and response to insulin in isolated mesenteric and epididymal adipocytes removed from fed or fasted male Wis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
3
9
0
1
Order By: Relevance
“…These data in humans are consistent with studies in overweight cafeteria-fed rats that demonstrated, after a 24 h fast, increased glycogen stores, lower glucose output and increased lactate uptake in the liver [240]. This brings us full circle to lactate as a possible important intermediate associated with the development of insulin resistance, particularly in obesity where it may well be excessively released from mesenteric adipose tissue [241][242][243][244] and provide a portal signal and substrate, accentuated after meals, for increased gluconeogenesis and glycogen synthesis.…”
Section: Implications For Type 2 Diabetessupporting
confidence: 89%
“…These data in humans are consistent with studies in overweight cafeteria-fed rats that demonstrated, after a 24 h fast, increased glycogen stores, lower glucose output and increased lactate uptake in the liver [240]. This brings us full circle to lactate as a possible important intermediate associated with the development of insulin resistance, particularly in obesity where it may well be excessively released from mesenteric adipose tissue [241][242][243][244] and provide a portal signal and substrate, accentuated after meals, for increased gluconeogenesis and glycogen synthesis.…”
Section: Implications For Type 2 Diabetessupporting
confidence: 89%
“…In fact, we found that tyramine weakly but significantly increased basal lactate release. Lactate release has been reported to be positively correlated with glucose uptake and glucose utilization (9). Our results are therefore in good agreement with previous reports which showed that tyramine and benzylamine were able to stimulate glucose transport and lipogenesis in rat adipose tissues by in vitro and in vivo studies (13,24).…”
Section: Discussionsupporting
confidence: 83%
“…First, basal lactate release is, under our conditions, already elevated: 3 to 4 fold higher than that observed in studies performed on younger rats (4). It is now well established that lactate release increases in large adipocytes from adipose tissues in old or obese rats (9) and it looks likely that, in our old rats (6-to 8-month old), basal lactate release reached its maximal capacity. A similar low stimulating effect observed with insulin may confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of labelled CO2 52 , and up to a degree, its incorporation in cells 53 or removal from the medium 54 have been used often with success. However, the studies using perfused 55 or perifused 56 organs and incubations with pieces of tissue 57 , now seldom used, have been the main methods available for analyses of the utilization of glucose and release of 3C units by live tissues.…”
Section: Discussionmentioning
confidence: 99%